Management of the land occupancy plan N°8 - Tiaret - TOUAIBIA, NARIMANE; BENLOKRICHI, MANAR; DIF, RANIA (University of Msila, 2024)
Urban expansions indicate the development and expansion of the city in terms of area and infrastructure to meet the needs of the overpopulation and to provide the necessary infrastructure for services and facilities. These expansions are an important part of urban planning and are aimed at improving the quality of life in the city and meeting the diverse needs of the population. The causes of urbanization vary from city to city and depend on local, economic, and social factors. Cities may expand due to population growth and demographic growth, with the population requiring additional housing, educational, health, and commercial facilities. Economic and industrial development can also create new jobs and attract more workers and migrants to the city. Urban expansions typically include the establishment and development of new residential areas and communities; the establishment of public facilities such as schools, hospitals, parks, and commercial centers; and the expansion of the city's infrastructure, such as roads, sewage networks, water, electricity, and public transport services. Urban expansion is a major challenge for urban planners and government officials, as it must be carefully coordinated and planned to ensure the future sustainability of the city. A balance must be struck between meeting the current needs of the population, preserving the environment and natural resources, and providing easy access to economic services and opportunities. The urbanization process must include comprehensive environmental, economic, and social impact studies and consultation with affected communities. Urban expansion must be implemented on the basis of long-term strategic plans aimed at achieving sustainable development and improving the quality of life of the city's population. Urban expansions should face challenges such as environmental pollution, traffic congestion, a lack of resources, and increasing illegal urban abuse. Therefore, urban expansion must be managed wisely and properly guided through the implementation of policies and actions that promote sustainability and maintain the balance between urban growth and the preservation of the environment and the city's cultural heritage. To achieve this, urbanization must rely on the principles of sustainable urban planning, such as the promotion of intensive and sustainable land use, the development of effective public transport, and the provision of green spaces and public parks. Architectural design that reflects local identity and preserves the cultural diversity of the city must also be encouraged.